(untitled) - Allen, James (Redwood City, Calif., 1995)
From a leading authority in artificial intelligence, this book delivers a synthesis of the major modern techniques and the most current research in natural language processing. The approach is unique in its coverage of semantic interpretation and discourse alongside the foundational material in syntactic processing.
Keywords: Ngôn ngữ lập trình (Máy tính điện tử),Programming languages (Electronic computers); Ngữ nghĩa,Semantics